A Toolkit for Out-of-Court Workouts - World Bank Group (World Bank, Washington, DC, 2017)
A Toolkit for Out-of-Court Workouts was created to achieve two objectives: (1) to provide policy makers with tools to develop a corporate restructuring framework and culture in their country; and (2) to help stakeholders implement informal corporate restructuring principles to try to rescue failing enterprises. It is accordingly aimed primarily at policy makers, financial institutions, and insolvency representatives, as well as enterprises. The Toolkit generally examines different models for restructuring, in the understanding that there is no such thing as a "one size fits all" approach, and countries have the ability to develop flexible and varied solutions to meet their specific financial sector needs. Specifically, the focus of the Toolkit is on workouts, which for the purposes of this publication is taken to mean two types of restructuring models: (1) those that involve no judicial involvement (i.e., that are purely out-of-court mechanisms [OCWs]); and (2) those that involve some institutional or judicial involvement (hybrid procedures). Focusing on these models is designed to provide stakeholders with a broader understanding of restructuring and the varied models that different countries are implementing. Included in the Toolkit are sample documents typically used in a workout. These are included only to illustrate certain practicalities and considerations in conducting a workout, and should not be used without legal advice in the jurisdiction of their intended use.